The Effects of Nitric Oxide on Blood Coagulation Process - raham armand; Goodarz Sadeghi Hashjin; ali Rassouli; Mozhgan Asghari (Fasa University of Medical Sciences, 2019)
Background & Objective: Nitric oxide (NO) in body can be made of amino acid L-arginine nitric oxide synthase (NOS). Donor drugs that release NO in the body are exogenous sources for this free radical. According to available sources, NO and its precursor (L-Arginine) can affect blood coagulation process. This work investigates the effect of NO on blood coagulation process in vitro using bovine blood as a model. Materials & Methods: Blood samples were taken from 5 apparently healthy adult Holstein cows and were separately exposed to ethylene diamine tetra acetic acid (EDTA) anticoagulation materials and sodium citrate. Then, the blood containing anticoagulation substance was incubated for 30 min at temperature of 37°C with 10, 100 and 1000 µM of donors of NO, including sodium nitroprusside (SNP), nitroglycerine (GTN), isosorbide dinitrate (ISDN). In addition, 1, 10 and 100 mM of substances affecting NOS (either L-Arginine, L-NAME or L-Arginine + L-NAME) were applied in relevant groups. After incubation, following general tests of coagulation were adopted: prothrombin time (PT), activated partial thromboplastin time (APTT), fibrinogen (FIB), hemoglobin (Hb), platelet count (PLT), red blood cell (RBC) count, mean corpuscular hemoglobin (MCH), mean corpuscular volume (MCV), mean corpuscular hemoglobin concentration (MCHC), hematocrit (HCT), white blood cells (WBC) count and methemoglobin (MetHb).  Results: Obtained results indicate that among all relevant works, combination of L-Arginine and L-NAME in applied concentrations can cause significant reduction of red blood cells and hemoglobin concentration (p<0.05). Despite some changes in other parameters, they did not reach the level of significance. Conclusion: In general, it could be mentioned that endogenous or exogenous NO in the model applied in this study may not have a decisive impact on blood coagulation process. However, the non-specific effects observed in the L-Arginine + L-NAME group on the number of red blood cells and hemoglobin concentration need further studies.